Islam and Local Wisdom: Integration of the Arab Community in Indramayu, Indonesia - Roni Tabroni (Cakrawala: Jurnal Studi Islam, 2020)
This article discusses the Arab community's efforts to integrate with local wisdom in Dermayu Village, Sindang, Indramayu. These values were then turned into principles, which have remained in place to this day. Leadership, ideological cultivation, and mobility are all considered in the research. The theory of Islamic social movements is used in this study to identify patterns of movement actors framing Islamic values and collaborating with local wisdom values. The findings revealed that Arab community actors were successful in fusing Islamic values with local wisdom by instilling the values of tolerance, cooperation, and accommodation. Two of the strategies used are da'wah and education. Assimilation and acculturation can be seen in everyday activities, indicating that people are attempting to fit into society. Furthermore, the community tries to avoid conflicts and disputes by participating actively in community activities such as election days, village meetings, and village management structures. They gain sympathy as a result of this issue, and they are able to live in peace.